ANALYSIS OF THE ROLE OF 112 SERVICES IN HANDLING CONFLICT BASED ON PUBLIC REPORTS IN THE COMMUNICATION AND INFORMATICS SERVICE OF MANADO CITY - Noldy Nofrie Damo; Steven V. Tarore; Devie S. R. Siwij (PT. Radja Intercontinental Publishing, 2026)
This study analyzes the role of the 112 Service of the Manado City Communication and Informatics Office in handling social conflicts based on public reports and identifies factors that influence its effectiveness. This study uses a qualitative approach with the interactive analysis method of Miles, Huberman, and Saldana (2019). Data were obtained through in-depth interviews with key informants from the Manado City Communication and Informatics Office, related agencies, and the community, supported by field observations and documentation studies. The results indicate that the 112 Service has played a strategic role as a mechanism for receiving reports, inter-agency coordination, and early control of social conflicts. However, this role is still reactive and facilitative, not fully proactive and executive. The early warning system still relies on direct reports from the public, and inter-agency coordination is still carried out manually. The effectiveness of the service is influenced by five main factors: institutional aspects, human resources, work systems and procedures, information technology support, and inter-agency coordination. These five factors together form a gap between the ideal concept of modern public services and their actual implementation in the field.